PENGARUH FAKTOR PSIKOLOGIS KONSUMEN TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN HANDPHONE MEREK SAMSUNG (Studi Kasus Pada Meteor Cell Malang) - Ahmad Zakaria; N. Rachma (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThis research was conducted to analyze the Consumer PsychologicalFactors on the Purchasing Decision of Samsung Mobile Brand (Case Study onMeteor Cell Malang). The formulation of the problem in this research is a declinein sales of products Hanphone Samsung for 3 months in a row. The independentvariable consists of motivation (X1), perception (X2), knowledge (X3), andattitude X4) dependent variable is Purchase Decision (Y). Sample amounted to100 respondents taken using explanatory research technique (explanatoryresearch). Analysts use SPSS 16.0 which includes, reliability test, validity test,Normality Test, classical assumption test, multiple regression analysis, hypothesistesting through F test and t test.Attitude variable shows the largest regression coefficient. Attitude is themost important factor affecting Samsung Mobile Brand Buying Decision (CaseStudy In Meteor Cell Malang). The third important factor is Knowledge, thenPerception as the fourth factor that affect the Purchase Decision.Keywords: motivation, perception, knowledge, and attitude, PurchaseDecision.